2021
DOI: 10.3928/01477447-20201202-04
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes of 3D-Printed Titanium Metaphyseal Cones in Revision Total Knee Arthroplasty

Abstract: Recently, 3-dimensional (3D) printing technology has been used in the development of titanium metaphyseal cones to manage severe bone loss in revision total knee arthroplasty (rTKA). This study assessed (1) radiographs; (2) functional outcomes; (3) complications; and (4) 2-year implant survivorship in patients receiving 3D-printed titanium metaphyseal cones for moderate-to-severe tibial and femoral bone loss in rTKA. A single institution, retrospective chart review was performed for patients with large bone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Three articles investigated the clinical outcomes of RTKA. Remily et al [ 15 ] and Tetreault et al [ 18 ] reported an improved Knee Society Scores (KSS) during the perioperative period, while Kong et al [ 16 ] indicated that the KSS scores of patients in the static group were not significantly different from the KSS score of patients in the articular group during admission. Both Remily et al and Tetreault et al reported good survivorship.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three articles investigated the clinical outcomes of RTKA. Remily et al [ 15 ] and Tetreault et al [ 18 ] reported an improved Knee Society Scores (KSS) during the perioperative period, while Kong et al [ 16 ] indicated that the KSS scores of patients in the static group were not significantly different from the KSS score of patients in the articular group during admission. Both Remily et al and Tetreault et al reported good survivorship.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of ten articles reported perioperative complications [ 15 , 18 , 19 , 21 24 ]. For RTKA surgery, perioperative complications mainly concerned aseptic loosening [ 15 ], periprosthetic fracture [ 18 ], and periprosthetic joint infection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remily et al. performed a retrospective analysis of 54 patients who underwent an rTKA from 2015 to 2017 for an AORI type II or III defect and were treated with a 3D-printed femoral or tibial porous titanium metaphyseal cone [ 52 ]. Patients had a minimum 2-year follow-up with a mean follow-up of 29.9 months (range 24–42 months).…”
Section: Management Of Bone Defectsmentioning
confidence: 99%